Trapping, sorting and transferring of micro-particles and live cells using electric current-induced thermal tweezers - Cong, Hengji; Chen, Jiajie; Ho, Ho-Pui (Sensors and actuators. B, Chemical, 2018)
•Transferring, sorting, separation and combination of particle clusters have been realized by selectively controlling the electrical drive current in the heating elements of the device.•In addition, live cells such as E. coli, have been showed to form clusters and manipulated at a target location based on the same mechanism.•The reported method offers a new approach for photon-free particle manipulation, while also holds promise for direct integration with lab-on-chip devices. We demonstrate the manipulation of micro-sized particles in water using Joule heating induced temperature gradient. Using simple sputter deposition and photolithography, we have fabricated disparate gold micro-structures on silica glass. Electric current crowding at narrow channels results in temperature gradients that can be readily controlled by varying the electric power input. This also, in turn, leads to a tunable balance between forces due to convective flow and thermophoresis in the surrounding aqueous medium. The net force can actually be used for trapping target objects. We have used the device to perform sorting, trapping and transferring of polystyrene sphere (PS) and live cells. The reported method offers a new approach for photon-free particle manipulation, while also holds promise for direct integration with lab-on-chip devices.